The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 15th ACM on International Conference on Multimodal Interaction 2013
DOI: 10.1145/2522848.2531746
|View full text |Cite
|
Sign up to set email alerts
|

Emotion recognition using facial and audio features

Abstract: Human Computer Interaction is an upcoming scientific field which aims at inter-communication between humans and computers. A major element of this field is Human Emotion Recognition. The most expressive way humans display emotions is through facial expressions. Traditionally, emotion recognition has been performed on laboratory controlled data. While undoubtedly worthwhile at the time, such lab controlled data poorly represents the environment and conditions faced in realworld situations. With the increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
(8 reference statements)
0
2
1
Order By: Relevance
“…In the context of naturalistic observations, Gómez Jáuregui and Martin (2013) applied FaceReader to analyse a dataset of acted facial expressions under uncontrolled conditions and found that the software could not accurately classify any expression. Contrasting with this result, Krishna et al (2013) achieved an expression classification accuracy of 20.51% using different automated methods with the same dataset, raising further questions about the performance of FaceReader in real-life recordings. Collectively, these studies contribute to the growing body of literature on the validity, limitations, and applications of AFC in understanding emotional facial expressions in diverse contexts, emphasising the importance of advancing AFC models to effectively capture and interpret facial expressions in realistic settings.…”
Section: Introductioncontrasting
confidence: 62%
“…In the context of naturalistic observations, Gómez Jáuregui and Martin (2013) applied FaceReader to analyse a dataset of acted facial expressions under uncontrolled conditions and found that the software could not accurately classify any expression. Contrasting with this result, Krishna et al (2013) achieved an expression classification accuracy of 20.51% using different automated methods with the same dataset, raising further questions about the performance of FaceReader in real-life recordings. Collectively, these studies contribute to the growing body of literature on the validity, limitations, and applications of AFC in understanding emotional facial expressions in diverse contexts, emphasising the importance of advancing AFC models to effectively capture and interpret facial expressions in realistic settings.…”
Section: Introductioncontrasting
confidence: 62%
“…Some attempts were made to use other appearance-based features, e.g. Local Gabor binary pattern from three orthogonal planes (LGBP-TOP) [2], optical flow and Gabor [17]. In addition, the geometric features were only used in [17].…”
Section: Introductionmentioning
confidence: 99%
“…Local Gabor binary pattern from three orthogonal planes (LGBP-TOP) [2], optical flow and Gabor [17]. In addition, the geometric features were only used in [17]. However, it is observed that the combination of optical flow, Gabor and geometric features work poorer than the baseline.…”
Section: Introductionmentioning
confidence: 99%